Pengaruh Kampanye Pemasaran Sosial pada Niat Perubahan Perilaku Masyarakat: Demografi sebagai Variabel Moderasi - Rully Arlan Tjahyadi; Nonie Magdalena; Laurensia Vina (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The Covid 19 pandemic that is currently hitting has caused anxiety for people around the world, including Indonesia. The Indonesian government has published various policies so that the country's survival can be maintained. Success in carrying out these policies requires collaboration between the government and the community so that behavior changes occur. Intention to change behavior is an important factor for the government's success in overcoming the crisis (Pandemic Covid-19). This study emphasizes the factors of social marketing campaigns as factors that influence social change intentions. Demographic factors based on gender, age, education level, and area of ​​residence are also variables that moderate the effect of social marketing campaigns on social change intentions. The data collection method used a survey with a questionnaire and the data analysis method used Moderated Regression Analysis. The results showed that social marketing campaigns had an effect on social change intentions with a significance level of 0.000. The results of testing the moderating variable show that the moderating variables for the categories of gender, education, and area of ​​residence strengthen the effect of social marketing campaigns on social change intentions. Meanwhile, demographic variables based on age category weaken the influence of social marketing campaigns social change intentions.